The Limitation of KPK’s Authority over BUMN Officials: Legal, Theoretical, and Institutional Implications - Pamungkas, Bayu Tri; Sakinah, Zurria (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study explores the legal and institutional consequences of limiting the authority of the Corruption Eradication Commission (KPK) in prosecuting corruption cases involving State-Owned Enterprises (BUMN), particularly after the enactment of Law No. 1 of 2025 and Law No. 19 of 2019. Using a normative juridical method that incorporates statutory analysis, conceptual frameworks, and relevant case studies, the research highlights a significant shift in the legal status of BUMN directors and commissioners. By no longer recognizing them as state administrators, the law effectively reduces the KPK's oversight capabilities and creates a potential legal vacuum. This shift poses a risk of enabling undetected corruption in strategic sectors of the economy and undermines public confidence in anti-corruption institutions. To bridge legal interpretation and institutional practice, this study draws from the theory of authority and institutional effectiveness. It emphasizes the need for clearer legal definitions and coherence in regulatory design. As a policy recommendation, the study calls for the revision of existing laws to restore the KPK’s functional oversight over BUMN officials and proposes a renewed interpretation of “state administrator” to align with anti-corruption objectives.